Ferrous Sulfate (Fe2+) Had a Faster Effect Than Did Ferric Polymaltose (Fe3+) on Increased Oxidant Status in Children With Iron-deficiency Anemia - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Objective: The purpose of this study was to compare the total oxidant and antioxidant effect of different oral iron preparations in children with iron-deficiency anemia (IDA). Methods: A total of 65 children with IDA were randomized to receive 5mg Fe/kg/d iron (II) sulfate (Fe2+ group, n = 33) or iron (III)-hydroxide polymaltose complex (Fe3+ group, n = 32); healthy controls (n = 28) were also included in the study. Serum total thiol (-SH), total antioxidant capacity (TAC), total oxidant status (TOS), oxidative stress index (OSI), and hematological profile were evaluated at the baseline and on day 8 and day 30 of the therapy. Results: Serum TOS and OSI levels were significantly higher and total -SH and total antioxidant capacity levels were significantly lower in the study groups at the beginning of therapy than in the controls (P > 0.001). In multivariate analysis, after controlling for multiple confounding factors, on days 8 and 30, serum TOS and OSI levels were not different in the Fe3+ group, whereas they were significantly reduced in the Fe2+ group (P <= 0.033). Conclusions: Serum total oxidant status was significantly increased in children with IDA, and Fe2+ was highly effective in correcting elevated oxidative status.
Keywords: anemia; iron deficiency; ferrous sulfate; ferric polymaltose; antioxidants; oxidants; oxidative stress; TOTAL ANTIOXIDANT CAPACITY; GLUTATHIONE-PEROXIDASE; OXIDATIVE STRESS; LIPID-PEROXIDATION; AUTOMATED-METHOD; ORAL IRON; RED-CELL; SUPPLEMENTATION; ERYTHROCYTES; THALASSEMIA